Raṅgaṇṭē iṣṭaṃ : sāhitī cintanalu - Tulasammā, Sī. (Houston, Texas : Vanguri Foundation of America, Inc, 2019)
Critical articles on Telugu literature.
In Telugu.
Keywords: Telugu literature -- 20th century -- History and criticism; Telugu literature; 1900-1999; Criticism, interpretation, etc